Dampak Pengumuman COVID-19 terhadap IHSG, Harga Saham, Abnormal Return dan Trading Volume Activity di Sektor Transportasi (Analisis Peristiwa di BEI 2019-2020) - Grenda Evi Kartikasari; Anita Carolina; Citra Lutfia (Fakultas Ekonomi Universitas Andalas, 2023)
In order to determine how the COVID-19 announcement affected the Indonesian Stock Exchange (BEI), this study examined IHSG, stock prices, abnormal returns as well as trading volume activity in the transportation industry from 2019 to 2020. Eighteen transportation companies were chosen for analysis over a 12-month period, centered around the event date of March 2, 2020, using purposive selection. The results demonstrate significant differences in IHSG and stock prices, but there are no significant distinctions in abnormal returns or trading volume activity prior and after the COVID-19 notificationt. This study contributes important new information about the complex ways that the pandemic has affected financial markets, particularly in the transportation sector.